2016
DOI: 10.1038/srep32377
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of non-canonical amino acids into the developing murine proteome

Abstract: Analysis of the developing proteome has been complicated by a lack of tools that can be easily employed to label and identify newly synthesized proteins within complex biological mixtures. Here, we demonstrate that the methionine analogs azidohomoalanine and homopropargylglycine can be globally incorporated into the proteome of mice through facile intraperitoneal injections. These analogs contain bio-orthogonal chemical handles to which fluorescent tags can be conjugated to identify newly synthesized proteins.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
84
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 38 publications
2
84
0
Order By: Relevance
“…meniscus destabilization) or joint development could lend insight into how matrix proteins form and reorganize during these processes. Recent studies indicate that HPG and AHA can incorporate into developing murine embryos33, supporting the potential scalability of FUNCAT analysis to such model systems.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…meniscus destabilization) or joint development could lend insight into how matrix proteins form and reorganize during these processes. Recent studies indicate that HPG and AHA can incorporate into developing murine embryos33, supporting the potential scalability of FUNCAT analysis to such model systems.…”
Section: Discussionmentioning
confidence: 83%
“…This investigation of the biosynthetic response to injury, disease, or altered genetic program could be performed either in vitro (as we assessed tissue engineered construct formation here) or in vivo . Previous studies have examined protein synthesis in drosophila and zebrafish systems and mice141533; scaling FUNCAT to mammalian systems with in vivo models of cartilage degeneration (e.g. meniscus destabilization) or joint development could lend insight into how matrix proteins form and reorganize during these processes.…”
Section: Discussionmentioning
confidence: 99%
“…[77] Contrarily to Eth, Aha is not toxic in mammalian cell lines, neither in whole organisms for short incubation times, and it has been used to selectively label the newly synthesized proteome via BONCAT. [57,79] These results provided a starting point for the differential reassignment of the N-terminus to Aha using the natural substrate preference of EcMetRS, while globally reassigning the internal AUG codons with Eth using the putative orthogonal SaMetRS / SatRNA Met pair.…”
Section: Separating Aug and Internal Aug Codons By Two Different Trnasmentioning
confidence: 97%
“…The attempts evolved from analysis of protein changes in various cells [32] to the alteration of newly synthesized proteomes in organs [33–34] and whole animals [35]. One of the major challenges accompanying this identification process is dealing with low abundances of newly synthesized proteins and their recognition and distinction from the pre-existing protein pool.…”
Section: Strategy and Methods To Identify Newly Synthetized Proteins mentioning
confidence: 99%
“…AHA and HPG labeling via intraperitoneal injection was recently used to characterize the proteome in developing mice [34]. First, it was demonstrated that in juvenile mice (25–35 days old), AHA and HPG incorporated into all tissues under investigation (heart, lung, brain, skeletal muscle and kidney) in dosage-dependent increase (0.025, 0.05 and 0.1 mg/g of AHA or HPG per day; 2 days of administration).…”
Section: Strategy and Methods To Identify Newly Synthetized Proteins mentioning
confidence: 99%